Employment Pattern of Migrant Labour in Punjab State: A Case Study (Indian Journal of Extension Education, 2017)
The study was undertaken with the objective to study the socio-economic profile of migrants, income, mode of migration and level of awareness of migrants for different schemes of central government. Three districts named Jalandhar, Mohali and Gurdaspur were selected. Gharuan and Bhago majra villages were selected from Kharar and Mohali blocks of District Mohali. Shahpur and Khiala villages were selected from Jalandhar and Adampur blocks of District Jalandhar. Bhumbli and Kot yograj villages were selected from Dhariwal and Kahnuwan blocks of district Gurdaspur. List of permanent and casual labourers was prepared from each village. From such list, a sample of 25 migrant labourers was prepared from each village. An interview schedule was prepared for collecting the response of migrants keeping in view of the objectives of the study. Thus the total sample comprised of 150 migrants for the present study. The findings of the study revealed that more than 3/4th of the respondents were in the age group of 0-30 years. The educational level of 79.33 per cent respondents was under matriculation. About 82.66 per cent of the respondents had family members of 5-8. More than half of the migrants were migrated from Bihar state. Out of 150 migrants, 126 were male. More than ¾ of the respondents were completely aware of Pradhan Mantri Jan Dhan Yojana. Age and awareness about Pradhan Mantri Jan Dhan Yojana shows strong positive linear relationship. The mean monthly income of migrants came out to be Rs 7658, Rs 9177 and Rs 7729 in Gurdaspur, Mohali and Jalandhar respectively.